A Systematic Review of Treatment for Children with Autism Spectrum Disorder: The Sensory Processing and Sensory Integration Approach - Jonathan Camino-Alarcón; Maria Auxiliadora Robles-Bello; Nieves Valencia-Naranjo; Aziz Sarhani-Robles (MDPI AG, 2024)
Background/Objectives: The prevalence of the diagnosis of autism spectrum disorder (ASD) has been increasing globally, necessitating updates to the Diagnostic and Statistical Manual of Mental Disorders with respect to ASD diagnosis. It is now recognised that ASD is related to sensory processing disorder, and sensory integration is considered a suitable intervention for treating children diagnosed with ASD. Methods: This paper provides a systematic review on a timeline from 2013 to 2023, based on the PRISMA model. Evidence was sought in the academic search engines Pubmed, Scielo, Eric, Dialnet, Springer, Base Search and Google Scholar, which produced 16 articles according to the inclusion criteria. Results: According to the results of this review, intervention with sensory integration in infants with ASD meets the criteria to be considered an evidence-based practice. The studies reviewed focused mainly on clinical settings and, therefore, we highlight the urgent need for further research to evaluate the effectiveness of sensory integration interventions in naturalistic settings such as homes and schools. Conclusions: This will help to obtain more representative data on how these interventions affect the daily lives of children with ASD.